2021
DOI: 10.1186/s40463-021-00501-5
|View full text |Cite
|
Sign up to set email alerts
|

Specimen oriented intraoperative margin assessment in oral cavity and oropharyngeal squamous cell carcinoma

Abstract: Objective Evaluate the oncologic outcomes and cost analysis of transitioning to a specimen oriented intraoperative margin assessment protocol from a tumour bed sampling protocol in oral cavity (OCSCC) and oropharyngeal squamous cell carcinoma (OPSCC). Study design Retrospective case series and subsequent prospective cohort study Setting Tertiary care academic teaching hospital … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
31
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(34 citation statements)
references
References 27 publications
2
31
1
Order By: Relevance
“…Further, beyond use versus nonuse, the method of intraoperative margin assessment has been found to have a considerable effect on final margin status. Horwich et al report a 93% relative reduction in risk of PSM with utilization of a specimen‐oriented protocol, as compared to a tumor bed frozen section protocol 21 . Trends and between‐group differences in the use of intraoperative margin assessment may have contributed to our findings.…”
Section: Discussionmentioning
confidence: 62%
See 1 more Smart Citation
“…Further, beyond use versus nonuse, the method of intraoperative margin assessment has been found to have a considerable effect on final margin status. Horwich et al report a 93% relative reduction in risk of PSM with utilization of a specimen‐oriented protocol, as compared to a tumor bed frozen section protocol 21 . Trends and between‐group differences in the use of intraoperative margin assessment may have contributed to our findings.…”
Section: Discussionmentioning
confidence: 62%
“…Horwich et al report a 93% relative reduction in risk of PSM with utilization of a specimen-oriented protocol, as compared to a tumor bed frozen section protocol. 21 Trends and between-group differences in the use of intraoperative margin assessment may have contributed to our findings. However, this data are not included in the NCDB.…”
Section: Discussionmentioning
confidence: 83%
“…In surgical oncological care, positive postoperative margins have been widely accepted as a prognostic factor for increased locoregional recurrence [ 60 ]. This has been endorsed in numerous studies of OPSCC, with patients who had final positive margins experiencing reduced disease-specific survival, recurrence-free survival, and overall survival [ 39 , 61 , 62 , 63 , 64 ]. However, all of these studies did not report HPV tumor status, which has been shown to be a crucial delineator when considering OPSCC outcomes [ 48 ].…”
Section: Discussionmentioning
confidence: 95%
“…First of all, since only a selected amount of the resection specimen is investigated, this lead to sampling error. As a result, sensitivity of frozen section is low (approximately 50%) which could lead up to 12.9% conversion from ‘negative’ margins by frozen section to ‘positive’ final histopathology margins [3,4]. Second, even if positive margins are found by frozen section, revising of initial positive margins to final negative histopathology margins using immediate intraoperative reresection was only achieved in 57.9% in a recent study [4].…”
Section: Introductionmentioning
confidence: 98%